Increased Nucleated Red Blood Cells Counts in Prolonged Rupture of Membranes is not Erythropoietin Driven - Barak, Sarit; Mimouni, Francis B.; Stern, Ruth; Cohen, Neta; Goldstein, Dana Barbing; Marom, Ronella (American Journal of Perinatology, 2015)
Objective The aim of this study is to examine the hypothesis that prolonged rupture of membranes (PROM) is associated with increased cord blood erythropoietin (EPO) concentrations, proportional to the duration of ruptured membranes.Study Design This study is a prospective, cross-sectional, observational (noninterventional) cohort study of mother–infant pairs. Criteria for inclusion were as follows: active labor with or without ruptured membranes and vaginally delivered neonates. Excluded were infants with major factors known to be associated with a potential increase in fetal erythropoiesis.Results A total of 40 mother–infant pairs were recruited. EPO was not influenced by duration of ruptured membranes and significantly correlated only with maternal body mass index.Conclusion Cord blood concentrations of EPO do not appear to be significantly affected by the duration of ruptured membranes. We speculate that erythropoiesis is upregulated in PROM by mechanisms that involve the production of cytokines and are not EPO driven.
Keywords: nucleated red blood cells; erythropoietin; prolonged rupture of membranes; cord blood